1994
DOI: 10.1128/jb.176.16.5086-5092.1994
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the citrate synthase (gltA) gene of Escherichia coli in response to anaerobiosis and carbon supply: role of the arcA gene product

Abstract: As an enzyme of the tricarboxylic acid cycle pathway, citrate synthase participates in the generation of a variety of cellular biosynthetic intermediates and in that of reduced purine nucleotides that are used in energy generation via electron transport-linked phosphorylation reactions. It catalyzes the condensation of oxaloacetate and acetyl coenzyme A to produce citrate plus coenzyme A. In Escherichia col this enzyme is encoded by the giA gene. To investigate how gitA expression is regulated, a gA4-lacZ oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 31 publications
10
83
0
Order By: Relevance
“…Since the ArcA and/or the Fnr proteins are known to regulate several TCA cycle genes, including the sdhCDAB, mdh, gltA, acnA, and fumAC genes, in E. coli in response to anaerobiosis (6,8,(16)(17)(18)(19)27), we examined the effects of arcA and fnr gene deletions on sucA-lacZ and sdhCDAB-sucA-lacZ expression (Table 4). In neither the arcA strain nor the fnr strain did sucA-lacZ expression vary significantly compared to that of the wild-type strain grown under aerobic or anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the ArcA and/or the Fnr proteins are known to regulate several TCA cycle genes, including the sdhCDAB, mdh, gltA, acnA, and fumAC genes, in E. coli in response to anaerobiosis (6,8,(16)(17)(18)(19)27), we examined the effects of arcA and fnr gene deletions on sucA-lacZ and sdhCDAB-sucA-lacZ expression (Table 4). In neither the arcA strain nor the fnr strain did sucA-lacZ expression vary significantly compared to that of the wild-type strain grown under aerobic or anaerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A 1.375-kb XhoI-BamHI DNA fragment (Fig. 1) containing the sequence encoding the 235-amino-acid C-terminal region of SdhB, the 300-bp sdhB-sucA intergenic region, and the sequence encoding the 123-amino-acid N-terminal region of SucA was isolated from plasmid pJTSD1 (18) and cloned into pGEM11f(ϩ) (Promega Inc.) to give pSJP39. The EcoRI-BamHI fragment of pSJP39 containing the above DNA region was then transferred into pRS414 and pRS415 to generate the sucA-lacZ protein (pSJP42) and the sucA-lacZ operon (pSJP43) plasmids, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We propose that ArcA phosphate occupancy of ArcA sites 1 and/or 2 may provide for the repression of gltA gene expression during anaerobic conditions ( Fig. 1; Park et al, 1994). Recent studies by Park et al (1997) have also shown that expression of the genes for two other TCA cycle enzymes, ␣-ketoglutarate dehydrogenase (sucAB ) and succinylCoA synthetase (sucCD ), are also controlled from the sdhC promoter.…”
Section: Fnr Acts As a Negative Regulator Of Sdhc Promoter Expressionmentioning
confidence: 88%
“…A more moderate inhibition occurs in the presence of excess glucose (160,170,193,212,(335)(336)(337)(338)(339)413).…”
Section: Limiting the Tricarboxylic Acid Cyclementioning
confidence: 99%